2009
DOI: 10.1007/s00441-009-0764-3
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholine inhibits nitric oxide (NO) synthesis in the gastropod nervous system

Abstract: Acetylcholine (ACh) is one of the main signals regulating nitric oxide synthase (NOS) expression and nitric oxide (NO) biosynthesis in mammals. However, few comparative studies have been performed on the role of ACh on NOS activity in non-mammalian animals. We have therefore studied the cholinergic control of NOS in the snail Helix pomatia and compared the effects of ACh on NO synthesis in the enteric nervous system of the snail and rat. Analyses by the NADPH-diaphorase reaction, immunocytochemistry, purificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…68,69 On the other hand, ACh is known to regulate nitric oxide synthase expression in mammals as well as in snail, another mollusk. 70,71 The observation here may suggest that regulation of nitric oxide by ACh may also occur in the chemotactile center of octopus.…”
Section: Discussionmentioning
confidence: 70%
“…68,69 On the other hand, ACh is known to regulate nitric oxide synthase expression in mammals as well as in snail, another mollusk. 70,71 The observation here may suggest that regulation of nitric oxide by ACh may also occur in the chemotactile center of octopus.…”
Section: Discussionmentioning
confidence: 70%
“…The temporary NOS blockade is not a consequence of the lack of substrate source or cofactors, since administration of L-arginine and NOS cofactors cannot restore NO synthesis in the enteric networks of dormant snails (Rőszer et al 2005). Some signals, such as monoamines and acetylcholine leading to depressed NOS activity, have also been identified (Rőszer et al 2005(Rőszer et al , 2009); however, the mechanisms behind diminished NOS activity are undefined.…”
Section: Discussionmentioning
confidence: 97%
“…Taqman assay was designed based on the cDNA sequence of Helix pomatia NOS (HelixNOS) according to Huang et al (1997). For primer sequence information, see Rőszer et al (2009). To compare relative levels of Helix-NOS mRNA in ganglia of active and dormant animals, we carried out a relative quantification method (Pfaffl 2006) using cyclophilin as an internal control.…”
Section: Methodsmentioning
confidence: 99%
“…A leading hypothesis on the biosynthesis of 1 and related compounds proposes that microorganisms are the true producers, synthesizing these compounds as a part of their symbiotic relationship with eukaryotic partners . The most convincing evidence supporting this hypothesis is the variability of toxicity from tetrodotoxin‐producing organisms held in captivity, implying that some unspecified external stimulant is necessary to elicit toxin production . Studies on the frog Atelopus varius and the fire‐bellied newt Cynops pyrrhogaster indicated that toxin levels were non‐detectable in captive‐raised organisms, whereas studies on the rough‐skinned newt, Taricha granulosa , have demonstrated an increase in toxin production while held in captivity.…”
Section: Receptor Site Imentioning
confidence: 99%